Factors Influencing Village Financial Management - Abubakar, Sukma; Bailusy, Muhsin N.; Buamonabot, Irfandi (AIBPM Publisher, 2024)
Good village financial management is the main foundation for improving village development and community welfare. The purpose of this study is to examine how village financial management in Bacan District, South Halmahera Regency, is impacted by leadership, human resources, commitment, and communication. This research uses quantitative methods by collecting data through surveys and questionnaires from 140 respondents from 14 villages in the research area. Analysis findings indicate that while communication has no discernible impact on village financial management, leadership, human resources, and dedication do. This research provides an important contribution in formulating strategies to increase accountability and transparency in village financial governance.